The unidimensional transient flow model applicable to real gas - Feng, Min (2008)
In this thesis, a general solution for the one-dimensional unsteady real gas flow is presented. The main difference of this approach with the traditional methods is to remove all the constraints based on ideal gas assumption and use the state properties of real gas. For simulating the real gas, a numerical model is generated based on three conservation equations describing the one-dimensional compressible flow, and a real gas property table in the recommended form is used to close the above equation set. The model is then solved using the two-step differential Lax-Wendroff method. All these techniques are coded in FORTRAN 77 into the subroutine POT of the computer program TSPARK.